1994
DOI: 10.1083/jcb.126.4.979
|View full text |Cite|
|
Sign up to set email alerts
|

A double leucine within the GLUT4 glucose transporter COOH-terminal domain functions as an endocytosis signal.

Abstract: Abstract. The unique COOH-terminal 30-arnino acid region of the adipocyte/skeletal muscle glucose transporter (GLUT4) appears to be a major structural determinant of this protein's perinuclear localization, from where it is redistributed to the cell surface in response to insulin. To test whether an underlying mechanism of this domain's function involves glucose transporter endocytosis rates, transfected cells were generated expressing exofacial hemagglutinin epitope (HA)-tagged erythrocyte/brain glucose trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 4 publications
3
58
0
Order By: Relevance
“…It is possible that the phosphorylation state of this site could regulate the interaction of the ␥ 2 L subunit with AP2 adaptin. Such regulation occurs with cluster of differentiation antigen 4 (CD4), the GLUT4 glucose transporter and CD3␥, in which the dileucine motif plays a role in clathrin-dependent endocytosis when a nearby serine is phosphorylated (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the phosphorylation state of this site could regulate the interaction of the ␥ 2 L subunit with AP2 adaptin. Such regulation occurs with cluster of differentiation antigen 4 (CD4), the GLUT4 glucose transporter and CD3␥, in which the dileucine motif plays a role in clathrin-dependent endocytosis when a nearby serine is phosphorylated (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…However, further mutational studies and kinetic analysis revealed that this motif was, in fact, required for efficient internalization (43,44). Thus the apparent lack of intracellular sequestration in these mutants resulted from an accumulation of GLUT4 at the plasma membrane because of a reduction in the rate of endocytosis.…”
Section: Identification Of Intracellular Glut4 Storagementioning
confidence: 95%
“…Steady-state and kinetic analysis of various expressed GLUT4 chimeric proteins have indicated that both the aminoand carboxyl-terminal domains are important in GLUT4 internalization from the plasma membrane (10 -15). In particular, the carboxyl-terminal dileucine motif (SLL) was found to substantially alter GLUT4 trafficking kinetics and steady-state localization (16,17). Although a specific GLUT4 sequence responsible for intracellular localization has yet to be identified, the presence of a carboxyl-terminal retention signal is consistent with the observation that expression of the GLUT4 carboxyl-terminal domain results in the translocation of the endogenous GLUT4 protein to the plasma membrane (18).…”
mentioning
confidence: 99%